Entre livres e oficiais a expansão do ensino normal em São Paulo (1927-1933) - Inoue, Leila Maria (Editora Oficina Universitária, 2021)
This book problematizes the history of primary teacher training in the state of São Paulo at a unique moment when the Escolas Normais Livres are recognized by the public authorities. It was through these institutions that the state expanded the number of teacher training schools after the 1927 Public Instruction Reform. Normais Livres to the Normal Official Schools to expand teacher training for the new urban centers that were formed in the interior and coast of the state. It is a work that questioned the moments of expansion of teacher education in São Paulo during the First Republic and sought to understand and analyze the process of expansion of Normal Schools Livres in the western region of São Paulo and the role of these institutions. For the construction of this narrative sources were raised privileged information such as laws, reports, teaching yearbooks, but also documents found in the permanent archives from the Leônidas do Amara Vieira State School, in Santa Cruz do Rio Pardo, and from the Nossa Senhora Auxiliadora College, in Lins, such as enrollment books, guest books, exam minutes, among others. This work emphasizes the importance of school collections and archives for investigations into the History of Education in Brazil.